Ultrasound findings in severe COVID-19: a deeper look through the carotid arteries - Bezerra,Camila Silva (2022)
Abstract Objective: To investigate vascular and perivascular abnormalities in the carotid arteries using ultrasound, as well as to evaluate their association with mortality and clinical variables in hospitalized patients with coronavirus disease 2019 (COVID-19). Materials and Methods: This was a prospective study in which 53 hospitalized patients with severe COVID-19 were evaluated and underwent carotid ultrasound. We documented the carotid ultrasound findings in these patients. Clinical, demographic, laboratory, and imaging features were analyzed and compared by statistical analysis to detect correlations between them. Results: Carotid ultrasound demonstrated luminal surface irregularity in 29 patients (55%), carotid plaques in 30 (57%), perivascular infiltration in four (8%), and increased intima–media thickness (IMT) in 31 (58%). Of the 31 patients with increased IMT, 19 (61%) died, and the association between increased IMT and COVID-19–related mortality was significant (p = 0.03). Logistic regression showed that the risk of death was 85% in patients who had increased IMT in combination with acute kidney injury at admission or a history of chronic kidney disease (p < 0.05). Conclusion: In hospitalized patients with severe COVID-19, carotid ultrasound can show increased IMT, luminal surface irregularity, carotid plaques, and perivascular infiltrates. The combination of increased IMT and kidney damage appears to increase the risk of death in such patients.